Pattern of dermatological manifestations among patients of rheumatic disorders at a tertiary care centre from Kashmir valley in North India - Sameem, Farah; Aleem, Samia; Sumaiya Majeed; Aslam, Aaqib; Fatima, Seerat; Manzoor, Sheikh (International Journal of Research in Dermatology, 2023)
Background: Various rheumatic disorders have cutaneous manifestations which sometimes precede systemic symptoms. These manifestations, therefore can act as diagnostic and prognostic markers of the rheumatic disorders. Understanding them may lead to early diagnosis, prompt treatment, and hence lower morbidity and mortality of the affected persons. The aims and objectives were to study the pattern of dermatological manifestations among patients of rheumatic disorders at a tertiary care centre from Kashmir valley in North India. Methods: Prospective observational study carried out in the department of Dermatology at SKIMS medical college in Kashmir valley in north India over a span of 12 months from July 2021 to June 2022. A sample size of 100 native Kashmiri patients of rheumatic disorders presenting to OPD with dermatological manifestations were included in the study. A detailed dermatological examination and history was taken. The various demographic data sought included age, gender, occupation, residence and clinical diagnosis. Each clinical entity was individually studied for specific features. Results: The mean age of presentation of rheumatic disorders was 33 years with the maximum number of patients (n=61) belonged to the age group of 20-40 years. Females outnumbered males (ratio of 1:2.225). Disorders like lupus and scleroderma were the most common rheumatic entity in this series. Besides these, vasculitis, Behcet’s disease, rheumatic arthritis, psoriatic arthritis and others also have significant cutaneous manifestations. Conclusions: Some rheumatic disease have significant cutaneous manifestations, understanding of which is essential for their proper management.